Biotechnology for Iron Ore Dump Remediation by Creating Steady Plants Associations - Mazur, A.Ye.; Kucherevskyi, V.V.; Shol, H.N.; Baranets, M.O.; Sirenko, T.V.; Krasnoshtan, O.V. (Science and Innovation, 2024)
A method for iron-ore dump biological remediation by planting steady multicomponent grassy associations similar to the natural steppe biogeocenotical structures has been developed. The models of fescue-feather-mixed grass associations for different types of dumps have been presented. The biotechnology of remediation has been suggested.